Analysis of a case of periodic alternating nystagmus. Issue 4 (April 1976) - Rudge, P; Leech, J
Abstract : A patient is described in whom there was periodic deviation of the eyes in darkness associated with alternating nystagmus. An exactly similar situation occurs in normal man subjected to a pendular stimulus. It is proposed that in this patient there was alternating activity of the vestibular nuclei on either side of the brain-stem as a result of a removal of cerebellar inhibition, and that this caused periodic shifts in the null region of Daroff and Dell'Osso.